Carbon Taxes and the Composition of New Passenger Car Sales in Europe - Nadirov, Orkhan; Vychytilová, Jana; Dehning, Bruce (MDPI, 2020)
This paper examines the effectiveness of implementing carbon taxes to reduce carbon dioxide emissions from transport. Using the system Generalized Method of Moments estimator, we utilize cross-country analysis for the first time to study the impact of carbon taxes on the composition of petrol versus diesel passenger cars sold in 17 countries over the period 2013–2017. The results suggest that increasing carbon taxes affects consumer behavior, causing a significant shift from petrol to diesel fuel vehicles, controlling for factors such as the price of passenger cars, fuel price, interest rates, income level, population density, inflation, and vehicle stock.
Keywords: Carbon tax.; Climate policy.; Automobile industry.